Gambaran Pengaruh Edukasi Kesehatan Gigi Menggunakan Video Animasi terhadap Pengetahuan Pencegahan Karies Gigi pada Siswa Sekolah Dasar di SDN Tunjungsekar 4 - Almas Tsaqif Figo Antoro; Dimas Dwi Yoga Saputra; Moh. Zainol Rahman (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Dental caries among children remains one of the most common oral health problems worldwide. School-age children are particularly vulnerable because of their limited understanding of proper oral hygiene and the frequent consumption of sugary foods. This study aimed to analyze the effect of dental health education using animated videos on the knowledge of dental caries prevention among fifth-grade students at SDN Tunjungsekar 4. The research employed a pre-experimental one-group pretest–posttest design involving 30 students, selected through total sampling. Data were collected using a structured questionnaire before and after the educational intervention. The results showed a notable improvement in students’ knowledge, with the percentage of those in the “good” knowledge category increasing from 3.3% to 70.0%. Statistical analysis using the Wilcoxon test indicated a p-value < 0.000, demonstrating a significant effect of the intervention. These findings suggest that animated video-based dental health education is an effective and engaging method for improving children’s understanding of dental caries prevention. Future studies are encouraged to include behavioral or skill-based variables and explore the use of educational game media to enhance learning outcomes.